DIFFERENCES IN THE INTENSITY OF MENSTRUAL PAIN USING WARM COMPRESS THERAPY AND LEMON (Citrus) AROMATHERAPY - Fathunikmah; Siska Helina; Larasati Irene Hendana (SEAJOM: The Southeast Asia Journal of Midwifery, 2023)
In 2020, interviews were conducted with female students from the Riau Poltekkes about the menstrual process they experienced. The survey results found that 20 female students experienced menstrual pain that interfered with their daily activities. This condition even interferes with learning activities. The purpose of this study was to determine the average difference in the intensity of menstrual pain using warm compresses compared to lemon (Citrus) aromatherapy. This type of research is Quasy Experiment. The research design is the Pre-Post Test Design. The research sample was taken using purposive sampling. 20 female students who experienced menstrual pain/dysmenorhea were given two types of compress therapy and lemon aromatherapy to find out whether there was a decrease in the intensity of the pain. Data analysis used the Mann Whitney-U statistical test at 95% confidence level. The results showed that the average menstrual pain intensity before applying warm compresses was 4.60 (SD = 1.174) and after it was carried out it was 1.60 (SD = 1.075). The average intensity of menstrual pain before lemon (citrus) aromatherapy was performed was 4.20 (SD = 1.309) and after it was performed it was 2.10 (SD = 1.287). The results of statistical tests with Mann Whitney-U showed no average difference between warm compresses and lemon (citrus) aromatherapy on menstrual pain.